Air Conditioner Repair Training As One Of The Skills To Enter The World Of Work/Entrepreneurship - Muhammad Guntur (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Having expertise is the main capital to be accepted for work, almost all companies set technical competency standards as one of the main indicators of work. Therefore, by participating in AC/air conditioning repair training, it can be a provision to be accepted to work in a company. Based on this explanation, this activity is aimed at teenagers in the village of Cipanas Lebak, Banten. This activity is intended to be a provision of skills, so that the trainees can compete in the world of work. The method of implementing the activity is the presentation of material and practice. The number of training participants was 50 people, consisting of young women and men. This activity was carried out for one full day, namely on June 25 2022 which is located on Jalan Raya Cipanas Lebak Banten, at the Cipanas Village Hall to be precise. The result of this activity was in the form of holding air conditioning/AC repair training activities which were attended by 50 Cipanas village youths. In addition, they get an understanding of the importance of having certain skills, in order to be accepted for work or to compete with other prospective workers. Furthermore, this activity can increase the participants' knowledge and technical expertise regarding AC repair procedures.